2022
DOI: 10.1093/molbev/msac263
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, Not Host Phylogeny, Shapes the Oral Microbiome in Closely Related Species

Abstract: Host-associated microbiomes are essential for a multitude of biological processes. Placed at the contact zone between external and internal environments, the little-studied oral microbiome has important roles in host physiology and health. Here we investigate the roles of host evolutionary relationships and ecology in shaping the oral microbiome in three closely related gorilla subspecies (mountain, Grauer’s, and western lowland gorillas) using shotgun metagenomics of 46 museum-preserved dental calculus sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…Susceptibility to infection often correlates with host phylogeny ( 56 , 57 ), although host ecology greatly influences microbiome community structure ( 34 , 58 ). Early studies of immune evolution suggested that AMPs were mostly generalist peptides with redundant function, suggesting that AMP variation was not caused by adaptive evolution ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to infection often correlates with host phylogeny ( 56 , 57 ), although host ecology greatly influences microbiome community structure ( 34 , 58 ). Early studies of immune evolution suggested that AMPs were mostly generalist peptides with redundant function, suggesting that AMP variation was not caused by adaptive evolution ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the evolution of immune genes is often interpreted with host phylogeny as a principle explanatory factor [7,46], host ecology can be a stronger driver of microbiome community structure [47]. Early studies of immune evolution suggested that AMPs were mostly generalist peptides with redundant function, suggesting AMP variation was not due to adaptive evolution [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we do not find a contribution of adaptive introgression to altitude adaptation, a phenomenon observed in humans and other species (Fontsere et al 2019; Witt and Huerta-Sánchez 2019). In mountain gorillas and eastern lowland gorillas at high altitude, this adaptation is likely driven by different mechanisms, such as the oral microbiome (Moraitou et al 2022).…”
Section: Discussionmentioning
confidence: 99%